Seed Longevity of Spotted Spurge and Wild Poinsettia Under Diverse Environmental Conditions - ASGARPOUR,R. (2020)
ABSTRACT: Seed longevity under different environmental conditions is considered as one of the most important factors in the spread and persistence of an exotic species. The Experiments were conducted to determine seed persistence in soil, effects of submergence in water, flooding of the soil, and high temperatures on germination and viability of spotted spurge (Chamaesyce maculata) and wild poinsettia (Euphorbia heterophylla) as two exotic species in different regions of Golestan province. Spotted spurge seeds buried at depth of 10 cm maintained their viability above 95% after a year, while wild poinsettia seeds were destroyed completely after exhuming the soil. Seeds of both species were unable to germinate under submergence, but 92% of the spotted spurge seeds remained viable under this condition for 14 d. No germination was observed after 9 weeks submersion. Submersion duration drastically affected seed germination of wild poinsettia, so that no germination occurred after 6 d submersion. Twelve days after flooding, spotted spurge emergence decreased by 57% compared to the control. Ten percentage of wild poinsettia seedlings emerged when flooding was kept up to 12 d after sowing, while control had 96% emergence. Germination of spotted spurge seeds subjected to 140 oC for 5 min was 5%. Viability of wild poinsettia seed was completely lost at 120 and 140 C for 5 min. These results suggest that spotted spurge is capable of forming persistent seedbank. Seeds of spotted spurge were partially tolerant to submersion in water, but wild poinsettia seed are susceptible to submergence. The burning of crop residue could also prevent augmenting the soil seed bank of both species.